Prognostic factors in colon cancer – what can we add to the standards? - Maliszewski, Daniel; Jastrzębski, Tomasz; Drucis, Kamil; Kopacz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2008)
An essential part of colorectal cancer treatment is total tumour resection. In a group of patients in whom we suspect increased risk of local recurrences or distant metastases, radiotherapy is recommended as an obligatory part of radical treatment and chemotherapy as a routine complementary treatment. Unfortunately, prognostic factors which are used nowadays do not allow us to divide patients into clinical groups, as far as prognosis is concerned. Recently, laboratory prognostic factors have become an increasingly important prognostic supplement, which may help us to close the gap created by imprecise clinical prognostic factors. Precise identification of unbeneficial prognostic factors would allow us to determine the group of patients who need more aggressive treatment and lead to increase in survival rate. This article is a short review of laboratory and clinical prognostic factors which may be helpful in planning optimal treatment in patients with colorectal cancer. We analyzed such laboratory factors as NLR (neutrophile lymphocyte ratio), CRP (C-reactive protein), monocytes, CEA (carcinoembryonic antigen) and D-dimer, and the following clinical factors: infiltration of the intestine wall, lymph node involvement, presence of distant metastases, Dukes Scale, grading and blood vessel infiltration. In conclusion, our findings clearly show that we are unable to evaluate the prognosis in patients with colorectal cancer correctly without analyzing both laboratory and clinical prognostic factors. Optimal prognostic factors should be easy available, well standardized and should work properly in every group of patients. This is the perfect description of laboratory prognostic factors which, however, need further investigation of their prognostic value. An indisputable advantage is also the fact that funds spent on additional laboratory tests (CRP, D-dimer) increase the cost of the whole diagnostics only by 50 zloty.